Since, the terms are in an AP, therefore
(3y + 5) - (3y - 1) = (5y + 1) - (3y + 5)
⇒ 6 = 2y - 4
⇒ 2y = 10
⇒ y = 5
∴ y = 5
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Arithmetic Progression- Don't miss these Questions56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation